Studying the Slide Pattern of Avalanches by Means of Photogrammetric Methods (L'Etude de l'Ecoulement des Avalanches de Neige par la Mise en Oeuvre de Methodes Photogrammetriques) - Kahn,Marcel (1972)
Contents: The slide of avalanches; Photogrammetric arrangement of the study; The site for the experiment; Work plan. Draft trans. from Axel Heiberg Expedition, McGill Univ., 1964 (sic).